Cortical reorganization following auditory deprivation predicts cochlear implant performance in postlingually deaf adults. Issue 1 (6th October 2020) - Sun, Zhe; Seo, Ji Won; Park, Hong Ju; Lee, Jee Yeon; Kwak, Min Young; Kim, Yehree; Lee, Je Yeon; Park, Jun Woo; Kang, Woo Seok; Ahn, Joong Ho; Chung, Jong Woo; Kim, Hosung
Abstract: Long‐term hearing loss in postlingually deaf (PD) adults may lead to brain structural changes that affect the outcomes of cochlear implantation. We studied 94 PD patients who underwent cochlear implantation and 37 patients who were MRI‐scanned within 2 weeks after the onset of sudden hearing loss and expected with minimal brain structural changes in relation to deafness. Compared with those with sudden hearing loss, we found lower gray matter (GM) probabilities in bilateral thalami, superior, middle, inferior temporal cortices as well as the central cortical regions corresponding to the movement and sensation of the lips, tongue, and larynx in the PD group. Among these brain areas, the GM in the middle temporal cortex showed negative correlation with disease duration, whereas the other areas displayed positive correlations. Left superior, middle temporal cortical, and bilateral thalamic GMs were the most accurate predictors of post‐cochlear implantation word recognition scores (mean absolute error [MAE] = 10.1, r = .82), which was superior to clinical variables used (MAE: 12.1, p  < .05). Using the combined brain morphological and clinical features, we achieved the best prediction of the outcome (MAE: 8.51, r = .90). Our findings suggest that the cross‐modal plasticity allowing the superior temporal cortex and thalamus to process other modal sensory inputs reverses the initially lower volume when deafness becomes persistent. The middle temporal cortex processing higher‐level language comprehension shows persistent negative correlations with disease duration, suggesting this area's association with degraded speech comprehensions due to long‐term deafness. Morphological features combined with clinical variables might play a key role in predicting outcomes of cochlear implantation. Abstract : Our findings suggest that the cross‐modal plasticity allowing the superior temporal cortex and thalamus to process other modal sensory inputs reverses the initially lower volume when deafness becomes persistent. The middle temporal cortex processing higher‐level language comprehension shows persistent negative correlations with disease duration, suggesting this area's association with degraded speech comprehensions due to long‐term deafness. Morphological features combined with clinical variables might play a key role in predicting outcomes of cochlear implantation.